2011
DOI: 10.1038/emboj.2011.262
|View full text |Cite
|
Sign up to set email alerts
|

The tumour antigen PRAME is a subunit of a Cul2 ubiquitin ligase and associates with active NFY promoters

Abstract: The human tumour antigen PRAME (preferentially expressed antigen of melanoma) is frequently overexpressed in tumours. High PRAME levels correlate with poor clinical outcome of several cancers, but the mechanisms by which PRAME could be involved in tumourigenesis remain largely elusive. We applied protein-complex purification strategies and identified PRAME as a substrate recognition subunit of a Cullin2-based E3 ubiquitin ligase. PRAME can be recruited to DNA in vitro, and genome-wide chromatin immunoprecipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 64 publications
7
71
0
4
Order By: Relevance
“…Targeting the Y/CCAAT box in cancer D Dolfini and R Mantovani transformed cells; the correlation is so impressive that in some tumors it is considered a prognostic marker (for a review see Eliseeva et al 71 and Costessi et al 133 ). Furthermore, the localization of YB-1 becomes strongly nuclear in tumor cells.…”
Section: The -Apparent -Paradox Of Y/ccaat Nf-y and Yb-1 In Cancermentioning
confidence: 99%
“…Targeting the Y/CCAAT box in cancer D Dolfini and R Mantovani transformed cells; the correlation is so impressive that in some tumors it is considered a prognostic marker (for a review see Eliseeva et al 71 and Costessi et al 133 ). Furthermore, the localization of YB-1 becomes strongly nuclear in tumor cells.…”
Section: The -Apparent -Paradox Of Y/ccaat Nf-y and Yb-1 In Cancermentioning
confidence: 99%
“…Information about PRAME expression and its prognostic value in HL is very limited. In a study performed by Staege et al [16] it was demonstrated that PRAME has been found to be expressed only in cell lines belonging to patients with resistant HL [17] . In the study performed by Willenbrock et al [18] , when patients with HL were compared with those with anaplastic large cell lymphomas and B cell non-Hodgkin lymphoma, PRAME expression was found to be higher in HL.…”
Section: Prame Expression and Its Clinicalmentioning
confidence: 98%
“…Inhibition of cell cycle arrest and differentiation may explain why PRAMEpositive cells are selected for during cancer progression, and interference with RA signaling may be pivotal for the establishment and maintenance of cancer stem cell phenotypes [1,17]. Recent in vitro studies have identified PRAME as a subunit of E3 ubiquitin ligase, and DNAbinding analyses support a role for PRAME in NFY-mediated transcriptional regulation [18]. Regulation of PRAME expression is thought to be, at least in part, controlled by methylation and other epigenetic silencing mechanisms.…”
Section: Prame Biology and Potential Role In Cancermentioning
confidence: 99%